Beneficial effects of combining nilotinib and imatinib in preclinical models of BCR-ABL(+) leukemias - Weisberg, Ellen (American Society of Hematology, 2007)
Drug resistance resulting from emergence of imatinib-resistant BCR-ABL point mutations is a significant problem in advanced-stage chronic myelogenous leukemia (CML). The BCR-ABL inhibitor, nilotinib (AMN107), is significantly more potent against BCR-ABL than imatinib, and is active against many imatinib-resistant BCR-ABL mutants. Phase 1/2 clinical trials show that nilotinib can induce remissions in patients who have previously failed imatinib, indicating that sequential therapy with these 2 agents has clinical value. However, simultaneous, rather than sequential, administration of 2 BCR-ABL kinase inhibitors is attractive for many reasons, including the theoretical possibility that this could reduce emergence of drug-resistant clones. Here, we show that exposure of a variety of BCR-ABL(+) cell lines to imatinib and nilotinib results in additive or synergistic cytotoxicity, including testing of a large panel of cells expressing BCR-ABL point mutations causing resistance to imatinib in patients. Further, using a highly quantifiable bioluminescent in vivo model, drug combinations were at least additive in antileukemic activity, compared with each drug alone. These results suggest that despite binding to the same site in the same target kinase, the combination of imatinib and nilotinib is highly efficacious in these models, indicating that clinical testing of combinations of BCR-ABL kinase inhibitors is warranted.